Relative anthropometric parameters as predictors of strength abilities of Olympic weightlifters - Valentin Panayotov; Krassimir Petkov; Rasho Makaveev (Journal of Coaching and Sports Science, 2026)
Background: Body proportions and muscular development are closely linked to force production capacity, yet their application as predictive tools in Olympic weightlifting training and athlete selection remains insufficiently explored. Aims: The study aimed to quantify the relationships between specific relative indexes of body muscularity and maximal force generated during two classic multi-joint resistance exercises – the back squat and the clean and jerk deadlift. Methods: 17 athletes participated in the study, all of whom were national-level competitors. Linear regression equations were estimated between four relative body muscularity parameters (Height/Body mass3 (BMH), Height/Shin circumference (HS), Height/Thigh circumference (HT), Height/Arm circumference (HA), and Height/Chest circumference (HC)) and maximal strength in back squat and clean and jerk deadlift. Results: We calculated statistically significant Pearson correlation coefficients and linear regression coefficients between the studied relative body muscularity parameters and maximal muscle strength in the back squat and deadlift. The adjusted R-squared values ranged from 0.082 to 0.768 across the regression equations. Conclusion: All studied relative parameters were statistically significant predictors of maximal strength in the deadlift and squat, with only 3 exceptions (BMH for the deadlift and BMH and HS for the squat). These results (in conjunction with the high adjusted R-squared values of the regressions) indicate that the constructed statistical models explain a relatively high proportion of the variation in the results. These findings can be used in training practice as guidelines for anthropometric changes to improve sports performance.